IFNγ-secreting T cells that highly express IL-2 potently inhibit the growth of intracellular M. tuberculosis in macrophages - Zhu, Liying; Wang, Bo; Gu, Jin; Zhou, Jiayu; Wu, Yuan; Xu, Wei; Yang, Min; Cai, Xia; Shen, Hongbo; Lu, Lu; Wang, Feifei (Frontiers in Immunology, 2024)
Cytokine of interferon-gamma (IFNγ) plays a vital role in the immune response against Mycobacteria tuberculosis (Mtb) infection, yet the specific function of T cells producing IFNγ in this process remains unclear. In this study, we first isolated IFNγ+CD3+ T cells induced by Mtb antigens using surface staining assays. which showed a strong ability to inhibit the growth of intracellular mycobacteria in macrophages. Peripheral blood mononuclear cells (PBMCs) from healthy individuals were then challenged with Bacillus Calmette–Guérin (BCG) or Mtb, respectively, to sort IFNγ-secreting T cells for mRNA sequencing to analyze the gene expression patterns. The results of the integrated data analysis revealed distinct patterns of gene expression between IFNγ+CD3+ T cells induced by the BCG vaccine and those induced by Mtb pathogens. Further, unlike Mtb-induced cells, BCG-induced IFNγ+CD3+ T cells expressed high levels of interleukin-2 (IL-2), which increased the frequencies of these cells and the production of effector cytokines IFNγ and IL-2. Our findings suggested that IFNγ+CD3+ T cells with high IL-2 expression presented potent effector functions to inhibit intracellular Mtb growth, while Mtb infection impaired IL-2 expression in IFNγ+CD3+ T cells.